Effects of 6-Weeks High-Intensity Interval Training in Schoolchildren with Insulin Resistance: Influence of Biological Maturation on Metabolic, Body Composition, Cardiovascular and Performance Non-responses - Alvarez, Cristian; Ramírez-Campillo, Rodrigo; Ramírez-Vélez, Robinson; Izquierdo, Mikel (Frontiers in Physiology, 2017)
Background: Previous studies have observed significant heterogeneity in the magnitude of change in measures of metabolic in response to exercise training. There is a lack of studies examining the prevalence of non-responders (NRs) in children while considering other potential environmental factors involved such as biological maturation. Aim: To compare the effects and prevalence of NRs to improve the insulin resistant level (by HOMA-IR), as well as to other anthropometric, cardiovascular, and performance co-variables, by early (EM) or normal maturation (NM) in insulin resistant schoolchildren after 6-weeks of HIIT. Methods: Sedentary children (age 11.4±1.7 years) were randomized to a HIIT-EM group (n=12) or HIIT-NM group (n=17). Fasting glucose(FGL), fasting insulin(FINS) and homeostasis model assessment of insulin resistant (HOMA-IR) were assessed as the main outcomes, as well as the body composition [body mass, body mass index (BMI), waist circumference (WC), and tricipital (TSF), supra-iliac(SSF) and abdominal skinfold(AbdSF)], cardiovascular systolic (SBP) and diastolic blood pressure (DBP), and muscular performance [one-repetition maximum strength leg-extension (1RMLE) and upper row (1RMUR) tests] co-variables were assessed before and after intervention. Results: There were no significant differences between groups in the prevalence of NRs based on FGL, FINS and HOMA-IR. There were significant differences in NRs prevalence to decreased co-variables body mass (HIIT-EM 66.6% vs. HIIT-NM 35.2%) and SBP (HIIT-EM 41.6% vs.HIIT-NM 70.5%). A high risk (based on Odds Ratios) of NRs cases was detected for FGL, OR = 3.2 (0.2 to 5.6), and HOMA-IR, OR=3.2 (0.2 to 6.0). Additionally, both HIIT-EM and HIIT-NM groups showed significant decreases (P < 0.05) in TSF, SSF, and AbdSF skinfold, and similar decreases in fasting insulin and HOMA-IR. Conclusion: Although there were no differences in the prevalence of NRs to metabolic variables between groups of insulin resistant schoolchildren of different maturation starting, other NRs differences were found to body mass and systolic BP, suggesting that anthropometric and cardiovascular parameters can be playing a role in the NRs prevalence after HIIT. These results were displayed with several metabolic, body composition, blood pressure, and performance improvements independent of an early/normal maturation or the prevalence of NRs.